2022
DOI: 10.1002/advs.202105184
|View full text |Cite
|
Sign up to set email alerts
|

Energy Saving and Energy Generation Smart Window with Active Control and Antifreezing Functions

Abstract: Windows are the least energy efficient part of the buildings, as building accounts for 40% of global energy consumption. Traditional smart windows can only regulate solar transmission, while all the solar energy on the window is wasted. Here, for the first time, the authors demonstrate an energy saving and energy generation integrated smart window (ESEG smart window) in a simple way by combining louver structure solar cell, thermotropic hydrogel, and indium tin oxides (ITO) glass. The ESEG smart window can ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 67 publications
0
32
0
Order By: Relevance
“…[192] In addition, Niu et al also designed a hydroxypropyl cellulose (HPC)-based thermochromic window that was combined with louver structure silicon solar cell (Figure 6d). [193] It was reported that the experimental power conversion efficiency of the cell was 17.89% (theoretical calculation: 18.24%). They also reported that the solar cell could supply the electricity to the thermochromic window to actively control the optical contrast.…”
Section: Multi-functional Smart Windowsmentioning
confidence: 97%
See 2 more Smart Citations
“…[192] In addition, Niu et al also designed a hydroxypropyl cellulose (HPC)-based thermochromic window that was combined with louver structure silicon solar cell (Figure 6d). [193] It was reported that the experimental power conversion efficiency of the cell was 17.89% (theoretical calculation: 18.24%). They also reported that the solar cell could supply the electricity to the thermochromic window to actively control the optical contrast.…”
Section: Multi-functional Smart Windowsmentioning
confidence: 97%
“…Reproduced with permission. [193] Copyright 2022, John Wiley & Sons. (e) Temperature-dependent current density-voltage diagrams of a smart window based on the (CH 3 NH 3 ) 4 PbI 6 • 2H 2 O perovskite (Figure 3).…”
Section: Multi-functional Smart Windowsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flexible gas sensors can be comfortably attached to human skin or surfaces, improving the applicability of gas detection. On the other hand, transparent stretchable gas sensors can be combined with transparent devices, such as smart windows, [117][118][119][120] to expand their application prospects. Below, we will introduce the latest development of transparent stretchable gas sensors.…”
Section: Transparent Stretchable Gas Sensorsmentioning
confidence: 99%
“…Explosive population growth and industrialization lead to the shortage of resources, the rapid exhaustion of fossil fuels and serious environmental pollution. [1][2][3] Therefore, the research on energy saving and environmental purification is of great significance, and has attracted great attention. 4,5 Sunlight is the main energy of our earth, providing enough energy for plant photosynthesis and heat for the atmosphere and water cycle.…”
Section: Introductionmentioning
confidence: 99%